2010
DOI: 10.1051/dst/2009056
|View full text |Cite
|
Sign up to set email alerts
|

Insolubility of milk powder products – A minireview

Abstract: -In this paper, the formation of insolubility in milk powder is described, and the factors affecting the reaction are discussed. The zone in which casein proteins are most sensitive to heat is in the moisture range that occurs during spray drying. The rate of reaction has been determined and shows differences of orders of magnitude with the moisture content. The effect of chemical reagents on the extent of reaction gives insights into the chemical bonds that inhibit hydration. Information on the drying of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Protein insolubility is initiated by the unfolding of whey proteins followed by aggregation with casein (Baldwin, 2010;Sharma et al, 2012;Straatsma, Van Houwelingen, Steenbergen, & De Jong, 1999) and in fat-containing systems this results in formation of protein-bridged fat globule clusters (Singh & Ye, 2010). Based on the previous research (De Ruyck, 1991;McKenna et al, 1999;Mol, 1975;Ohba, Takahashi, & Igarashi, 1989) the formation of insoluble material is hypothesised to originate from heat and shear applied during spray drying resulting in changes in fat-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Protein insolubility is initiated by the unfolding of whey proteins followed by aggregation with casein (Baldwin, 2010;Sharma et al, 2012;Straatsma, Van Houwelingen, Steenbergen, & De Jong, 1999) and in fat-containing systems this results in formation of protein-bridged fat globule clusters (Singh & Ye, 2010). Based on the previous research (De Ruyck, 1991;McKenna et al, 1999;Mol, 1975;Ohba, Takahashi, & Igarashi, 1989) the formation of insoluble material is hypothesised to originate from heat and shear applied during spray drying resulting in changes in fat-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen solubility index (NSI); dispersability and heat stability of 32 commercial MPC powders were widely varied in the range of 27-87%; 38-100% and 0-42 min, respectively (Huppertz and Gazi 2015). Baldwin (2010) reported that poor solubility of MPC powders continued to be a problem by negatively affecting other functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…During drying of SMP and WMP, lactose prevents protein-protein interaction as it acts as a mechanical spacer; forms hydrogen bonds with protein chains and also provides channel for absorption of water molecules within casein micelles during reconstitution process, resulting in better solubility (Baldwin 2010). Passage of lactose into permeate during UF treatment, minimizes retentates protection during drying; resulted in poor solubility of MPC powders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor reconstitutability of these powders is mainly due to slow release of casein micelles from the powder particle as it has been shown that the slowly solubilising material consists almost entirely of caseins, whereas the whey proteins, lactose and minerals are readily soluble (Anema et al, 2006;Havea, 2006;Mimouni et al, 2010a). Caseins are aggregated via non-covalent bonding (Anema et al, 2006;Baldwin, 2010;Havea, 2006). Microstructural analysis shows that with increased storage time the casein micelles increasingly interact with each other, especially on the surface of the powder particle, leading to "skin" formation, slowing down the release of the casein micelles from the dispersed powder particles (Mimouni, Deeth, Whittaker, Gidley, & Bhandari, 2010b).…”
Section: Introductionmentioning
confidence: 99%